The Roles Of Investor Sentiment In Malaysian Stock Market - Tuyon, Jasman; Ahmad, Zamri; Matahir, Hylmee (Asian Academy of Management (AAM), 2016)
The objective of this work is to offer an alternative theoretical perspective and modelling of local investor sentiment proxies in Malaysian stock market. In the theoretical part, two alternative theoretical perspectives in understanding sentiment are introduced, namely, the cognitive-affective theory of mind from neuroscience and the ABC model of the cognitive psychology. In modelling, we identify a combination of survey-based and market-based investor sentiment proxies, namely, the consumer sentiment index, the business condition index, and the stock futures index. The validity of the theory and model is then falsified with empirical analysis by examining the long- and short-run as well as stability relationships of the sentiment proxies on the aggregate stock market index returns using suitable econometric methods. The findings revealed that the proposed sentiment proxies are statistically significant in relations to the stock market returns in the long- and short-run with varying degree of persistency. However, the relations are not homogeneous across different size, industry groups, and market states which are in line with the existing behavioural finance views. In summary, this paper provides a new theoretical insights and empirical evidence on the roles of sentiment in Malaysian stock market that offers valuable academic, practical and policy implications.